INDONESIAN CRIMINAL LAW INTEGRATING MAQĀṢID AL-SYARĪ‘AH : with Ibn ‘Āsyūr's Theological Approach to Qiṣāṣ and Theft - muhammad dakhlan gazali (Malang Prodi. Ahwal Al-Syakhsiyyah, IAI Al-Qolam, 2025)
Keywords: maqāṣidal-syarī‘ah, Ibn ‘Āsyūr, 2023 Criminal Code, Indonesian criminal law, qiṣāṣ, theft.